Effect Of Profitability and Good Corporate Governance On Firm Value With Corporate Social Responsibility As An Intervening Variable - Deni Ariadi; Siti Sundari (Green Publisher Indonesia, 2024)
The company was founded with a goal, one of which is to improve the welfare of its shareholders. By increasing the company's share price, the company's value in the eyes of investors will also increase. The value of a company can be seen from the Tobin'Q ratio. Companies registered in LQ 45 have quite high company value. The aim of this research is to analyze the influence of profitability and GCG on company value through CSR as an intervening variable. This research is a type of associative research with a quantitative approach. The object of this research is the LQ 45 company listed on the IDX for the 2018–2022 period. Sampling in this study used a purposive sampling method and 20 companies were found that met the sample criteria. This research uses secondary data in the form of Sustainability reports and company annual reports. This research uses the path analysis method using SPSS as an analysis tool. The results of this research show that: (1) Profitability has a positive and significant influence on company value. (2) GCG has a positive and insignificant influence on company value. (3) CSR has a significant positive influence on company value. (4) Profitability has a positive and significant influence on company value throught CSR. (5) GCG has negative and insignificant influence on company value throught CSR.